Problematika dan Rekonstruksi Kebijakan Pembelajaran Pendidikan Agama Islam - Mutia Rahmah; Khairunnisa Khairunnisa; Aisyah Maulidia; Nuryadin Nuryadin (Takuana: Jurnal Pendidikan, Sains, dan Humaniora, 2026)
This study aims to analyze the problems underlying Islamic Religious Education (IRE) learning policies and formulate a reconstruction framework from the perspective of Islamic Education Management. Despite its strategic role in character development, IRE continues to face challenges related to curriculum rigidity, limited teacher professionalism, digital transformation, and policy implementation. This study employed a qualitative library research approach through literature review and policy document analysis. Data were collected from fifteen relevant academic sources, including journal articles, books, and educational policy documents published between 2019 and 2026. The findings reveal that the implementation of IRE learning policies is constrained by four major managerial weaknesses: inadequate human resources, limited digital adaptation, weak stakeholder collaboration, and the absence of systematic strategic planning. To address these issues, the study proposes a policy reconstruction framework based on four principles of Islamic Education Management: itqan (professionalism), syura (consultation), taghyir (adaptive change), and tashwir (strategic planning). The framework integrates Islamic values with contemporary managerial functions to support more effective and sustainable policy implementation. The study recommends the development of flexible, technology-oriented, and collaborative IRE policies to improve the quality and relevance of Islamic education in the contemporary era.